Energy saving: role and place in energy strategy of Ukraine - Zhovtyansky V.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2001)
The decisive role and place of the energy saving as factor of perspective energy strategy of Ukraine is shown. The main problems during implementation of energy saving in national economy in particular in fuel and energy complex are determined. The ways of increase of energy efficiency and its legislative and normatively-technical introduction in limits of approaches forming of energy strategy creation of Ukraine up to 2030 are proposed.